Classification of Personnel Procedures in the National Police of Ukraine - Солнцева, Христина Володимирівна; Солнцева, Х. В.; Solntseva, Khrystyna V.; Куракін, Олександр Миколайович; Куракін, О. М.; Куракин, Александр Николаевич; Kurakin, Oleksandr M.; Чанишева, Аліна Рашидівна; Чанишева, А. Р.; Чанишева, Алина Рашидовна; Chanysheva, Alina R.; Собакарь, Андрій Олексійович; et al. (Editorial Primmate S. A. S., 2020)
The purpose of the article is to explore the types of personnel procedures in the National Police of Ukraine on the basis of scientific developments of scholars and to carry out their classification. To achieve this goal, such methods as formal-logical, comparative analysis, system-structural and comparative-legal was used. The successful functioning the National Police of Ukraine is not possible without the proper selection of highly qualified employees, which can be ensured through the introduction of truly effective and efficient personnel procedures. The theoretical and legal approaches to the division of personnel procedures into appropriate types by different classification criteria are analyzed and summarized, in particular, depending on: a) the subject of the initiative; b) the nature of the consequences; c) the type (direction) of the activity of the authority. The personnel procedures, which are divided into ordinary and simplified, are also illustrated. The tasks of the National Police Personnel Department are given. It is stated that the achievement of effective work of the National Police bodies is not possible without further improvement of the mechanism of personnel procedures, since insufficient work with staff has a negative impact on the reform of this law enforcement agency. As a result of the study the author's classification of personnel procedures in the National Police of Ukraine was proposed, namely, according to the following criteria: 1) by the subject of the initiative of the personnel procedure; 2) by the nature of the consequences for the subject of the personnel relations; 3) by the stage of staffing; 4) by the direction of activity of the subject of personnel relations in the police force; 5) by the degree of regulation; 6) by functional purpose; 7) by tasks of staffing.

Мета статті полягає в тому, щоб на підставі наукових розробок учених дослідити види кадрових процедур в Національній поліції України та здійснити їх класифікацію. Для досягнення поставленої мети використано такі методи, як формально-логічний, порівняльного аналізу, системно-структурний та порівняльно-правовий. Успішне функціонування Національній поліції України не можливе без належного відбору високопрофесійних працівників, що забезпечується шляхом запровадження ефективних і дієвих кадрових процедур. Проаналізовано та узагальнено теоретико-правові підходи до поділу кадрових процедур. Виділено відповідні їх види за різними класифікаційними критеріями, зокрема залежно від: а) суб’єкта ініціативи; б) характеру наслідків; в) виду (спрямованості) діяльності органу. Також наведені кадрові процедури за ступенем урегульованості, які поділяються на звичайні та спрощені. Приведені завдання Департаменту кадрового забезпечення Національної поліції. Констатовано, що досягнення ефективної роботи органів Національної поліції неможливе без подальшого вдосконалення механізму кадрових процедур, оскільки низька робота з персоналом негативно позначається на реформуванні даного правоохоронного органу. У результаті проведеного дослідження запропоновано авторську класифікацію кадрових процедур в Національній поліції України, а саме за наступними критеріями: 1) за суб’єктом ініціативи проведення кадрової процедури; 2) за характером наслідків для суб’єкта кадрових правовідносин; 3) за стадією кадрового забезпечення; 4) за спрямованістю діяльності суб’єкту кадрових правовідносин в органах поліції; 5) за ступенем урегульованості; 6) за функціональним призначенням; 7) за завданнями кадрового забезпечення.
Solntseva K. V. Classification of Personnel Procedures in the National Police of Ukraine / K. V. Solntseva, O. M. Kurakin, A. R. Chanysheva, A. O. Sobakar // Amazonia Investiga. – Vol. 9. – Iss. 28. – Editorial Primmate S. A. S., 2020. – P. 100-107.
Keywords: police; National police; personnel; personnel procedure; types of procedures; поліція; Національна поліція; кадри; кадрова процедура; види процедур; Research Subject Categories::LAW/JURISPRUDENCE